Representasi Nilai Kearifan Ranggawarsita pada Kepemimpinan Kepala Dinas Penerangan Komando Armada II dalam Mewujudkan World Class Navy - Prasadana, Afrizal; Purwanto, Purwanto (representamen, 2020)
Public relations (PR) has an important focus on the ability of a public relations practitioner to carry out leadership functions. The importance of a quality and value of leadership in the world of public relations (excellent leadership in public relations) in managing an organization. On the other hand, leadership in general is universal, but leadership in public relations practice is contextual. Specifically, the context of this research on how the leadership carried out by the head of the Information Service Fleet Command II represents the value of wisdom contained in the fiber and philosophy of life of Ranggawarsita which is applied to internal and external public in order to realize the Navy World Class. Through the constructivist paradigm, researchers conduct qualitative data collection and are processed through descriptive research. The results of this study indicate, (1). Referring to Panca Pratama, the concept of maintaining good relations between public relations leaders and their public, is in accordance with the concept of Amilala (which means to maintain) (2). In making a decision, the head of the office is the head of the information service or the commander of the Koarmada who takes over and all parts of the organization must carry out. This relates to the Javanese concept of accepting pandum. (3). The head of the information service has a positive attitude and outlook on life, so that subordinates will always melu handarbeni, hangrungkebi melu, mulat sarira hangrasa wani in the sense that all achievements obtained by the organization will always be well developed by subordinates. Keywords: Public Relations, Leadership, Koarmada II, Local Wisdom, Ranggawarsita